Pedagogie comparate - Mario Gennari (Firenze University Press, 2019)
The article proposes to present the disciplinary area in which could be placed a research field not studied yet. The name could be "Comparative Pedagogies". This science is focused on the pedagogical theories and practices in their respective identities and differences, through comparisons of different kinds: (i) historical and geographical; (ii) anthropic, social and psychic; (iii) economic, political and legal; (iv) linguistic, literary and artistic; (v) mythological, esoteric, religious, philosophical and scientific.